Potentially hazardous waste produced at home - Chaves, Loide Corina; De Campos, Ligia Mara Daros; Filipini, Rosangela; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Azzalis, Ligia Ajaime; Junqueira, Virginia Berlanga Campos; Sena, Dayse F; Goulart, Flávia C; Fonseca, Fernando Luiz Affonso (Springer Nature, 2013)
Background: The purpose of this study was to identify the sources of waste generation household consisting of biological material and to investigate the knowledge presented by those responsible for the generation of waste in the home environment on the potential health risk human and environmental. Method. It is a quantitative survey performed in Parque Capuava, Santo André (SP). The questionnaire was administered by the community employers and nursing students during the consultation with nursing supervision through interview question/answer. The exclusion criteria were patients who were not in the area served by the Basic Health Unit which covers the area of Pq Capuava. The sample was consisted of 99 persons and the data collection a questionnaire was used. Results: We observed that 63.3% of people said to use disposables, with the majority (58.7%) of these use the public collection as the final destination of these materials. It was reported that 73.7% of those surveyed reported having knowledge about the risk of disease transmission. Public awareness of the importance of proper packaging and disposal of potentially hazardous household waste may contribute significantly to the preservation of human and environmental health and this procedure can be performed and supervised by professional nurses. Conclusion: We suggest implementation of workshops for community health workers and the general population in order to enhance their knowledge about the storage and disposal of potentially infectious waste generated at home, thereby reducing the potential risk of disease transmission by improper management. © 2013 Chaves et al.; licensee BioMed Central Ltd.
Keywords: Environmental health; Housing; Medical waste; biomaterial; adult; awareness; community care; consultation; controlled study; disease transmission; domestic waste; employer; environmental exposure; environmental health; female; hazardous waste; health auxiliary; health center; health hazard; health survey; home; home environment; housing; human; male; normal human; nursing; nursing student; packaging; preservation; professional practice; public health; questionnaire; risk factor; storage; waste disposal; workshop